Effects of Sodium-Glucose Transporter 2 Inhibitors (SGLT2-I) in Patients With Ischemic Heart Disease (IHD) Treated by Coronary Artery Bypass Grafting via MiECC: Inflammatory Burden, and Clinical Outcomes at 5 Years of Follow-Up - Sardu, Celestino; Massetti, Massimo; Testa, Nicola; Martino, Luigi Di; Castellano, Gaetano; Turriziani, Fabrizio; Sasso, Ferdinando Carlo; Torella, Michele; De Feo, Marisa; Santulli, Gaetano; Paolisso, Giuseppe; Marfella, Raffaele (Frontiers in Pharmacology, 2021)
Introduction: Minimally invasive extracorporeal circulation (MiECC) reduced inflammatory burden, leading to best clinical outcomes in patients treated with coronary artery bypass grafting (CABG). Despite this, the patients with type 2 diabetes mellitus (T2DM) vs those without T2DM (non-T2DM) have a worse prognosis, caused by over-inflammation and modulated by sodium-glucose transporter 2 receptors. However, we evaluated the inflammatory burden and clinical outcomes in non-T2DM vs T2DM patients under sodium-glucose transporter 2 inhibitors (SGLT2-I users) vs non-SGLT2-I users at 5 years of follow-up post-CABG via MiECC. Materials and methods: In a multicenter study, we screened consecutive patients with indications to receive CABG. The study endpoints were the inflammatory burden (circulating serum levels of tumor necrosis factor-alpha (TNF-α), interleukin 1 and 6 (IL-1 and IL-6), C-reactive protein (CRP), and leucocytes count) and the clinical outcomes at follow-up of 5 years in non-T2DM vs SGLT2-I users, in non-T2DM vs non-SGLT2-I users, and SGLT2-I users vs non-SGLT2-I users. Results: At baseline, and at one year and 5 years of follow-up, the non-T2DM vs SGLT2-I users, non-T2DM vs non-SGLT2-I users, and SGLT2-I users vs non-SGLT2-I users had the lowest values of IL-1, IL-6, and TNF-α (p < 0.05). At one year of follow-up, SGLT2-I users vs non-T2DM and non-SGLT2-I users vs non-T2DM users had a higher rate of all deaths, cardiac deaths, re-myocardial infarction, repeat revascularization, and stroke, and of the composite endpoint (p < 0.05). In a multivariate Cox regression analysis, the composite endpoint was predicted by IL-1 [2.068 (1.367–3.129)], TNF-α [1.989 (1.081–2.998)], and SGLT2-I [0.504 (0.078–0.861)]. Conclusion: In T2DM patients, the SGLT2-I significantly reduced the inflammatory burden and ameliorated clinical outcomes at 5 years of follow-up post-CABG via MiECC.